فصل المقال فيما بين أدب الرحلة والإثنوغرافيا من اتصال - درنوني, سليم; حماني, علي (Changement Social; No 4 (2018): revue change social, 2018)
هناك اعتراف لدى بعض مفكري أوروبا بتأثير التراث الحضاري العربي على الحضارة الغربية الحديثة، يقابل هذا الاعتراف تنكر لهذه الحقيقة التاريخية، من خلال السعي نحو طمسها، أو التقليل من شأنها لدى البعض الآخر. لهذا من الضروري العمل على فحص التراث العربي، بتنوعه وغزارته ودراسته دراسة متأنية ومتعمقة، لا سيما تلك الأعمال ذات الصلة المباشرة بالأنثروبولوجيا، قد تؤدي هذه الدراسات إلى إعادة تاريخ الأنثروبولوجيا من جديد، أو على الأقل، إعادة أصولها المعرفية والمنهجية، بحيث لا ترد جميعها إلى عصر النهضة (التنوير) في أروبا فحسب، بل قد يوجد في التراث الحضاري العربي الكثير من المفهومات والنظرات عن الجنس البشري والحضارة الإنسانية، وأوجه الحياة اليومية ومشكلاتها، مما لا يزال يشغل بال الباحثين الأنثروبولوجيين المعاصرين على حد تعبير الباحث السوري عيسى الشماس. There is recognition among some thinkers of Europe, the impact of the Arab cultural heritage to modern Western civilization, offset by the recognition deny this historical fact, through the pursuit of obliterating, or underestimated among others. This is why it is necessary to work on the examination of Arab heritage, diversity and abundance, study careful study and in-depth, especially those directly related to the science of anthropology work, these studies may lead to a re-history of anthropology of a new, or at least re-knowledge and the methodology of its assets, so they do not respond all Renaissance européenne  only, but may exist in the Arab cultural heritage a lot of perceptions and insights about the human and human civilization sex, and aspects of daily life and its problems, which are still preoccupied anthropologists researchers contemporaries in the words of Syrian researcher Aissa Achemmasse.